Human Miscarriage Is Associated With Dysregulations in Peripheral Blood-Derived Myeloid Dendritic Cell Subsets - Ehrentraut, Stefanie; Sauss, Karoline; Neumeister, Romy; Luley, Lydia; Oettel, Anika; Fettke, Franziska; Costa, Serban-Dan; Langwisch, Stefanie; Zenclussen, Ana Claudia; Schumacher, Anne (Frontiers in Immunology, 2019)
Dendritic cells (DC) are critically involved in decisions related to the acceptance or rejection of the foreign fetal antigens by the maternal immune system. However, particularly for human peripheral blood DCs (PBDC), available literature is rather inconsistent and the factors regulating these cells are ill-defined. Here, we investigated the phenotype and functionality of different human PBDC subsets during normal and pathologic pregnancies and studied an involvement of human chorionic gonadotropin (hCG) in PBDC regulation. Peripheral blood samples were obtained from normal pregnant women in all three trimesters, from first trimester miscarriage patients and from healthy non-pregnant women. Samples were analyzed for plasma hCG levels, for regulatory T (Treg) cell numbers, for frequencies of total and mature plasmacytoid (PDC) and myeloid (MDC1 and MDC2) PBDC subsets and for their cytokine secretion. In vitro assays, culturing PDC, MDC1 or MDC2 in the presence of two trophoblast cell lines, placenta explant supernatants or two hCG preparations were performed. The Treg-inducing capability of hCG- or non-hCG-treated stimulated MDC1 was assessed. Total and mature MDC1 and MDC2 frequencies increased during the first and second trimester of normal pregnancy, respectively. Miscarriage was associated with a reduced MDC1 and an increased MDC2 activation profile. PDC were not altered neither during normal pregnancy progression nor during miscarriage. In vitro, the culture of isolated PBDC subsets in the presence of placenta-derived factors impaired the maturation of MDC1 and differentially affected PDC maturation. An inhibitory effect on MDC1 and PDC maturation was also proven for the urine-derived hCG preparation. Finally, we observed a Treg cell elevation during early normal pregnancy that was not present in miscarriages. Stimulated MDC1 induced Treg cells in vitro, however hCG was not involved in this process. Our findings suggest that during normal pregnancy PBDC subsets are differentially regulated dependent on gestational age. Miscarriage seems to be associated with dysregulations in the myeloid PBDC subsets and with disturbances in Treg cell frequencies. Moreover, our results propose an interdependency between MDC1 and Treg cells during early pregnancy. hCG, although shown to impair MDC1 maturation, does not seem to be a key regulator of PBDC alterations during pregnancy.